Tetradrachms and Didrachms of Sophytos - Taylor , Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2024)
A die study of the large denomination coinage bearing the legend SWΦΥTOY (of Sophytos) provides new insights into the development of the coinage. It was struck from three tetradrachm and two didrachm obverse dies. These large denominations were the mainstay of military and mercenary payments. Mintage from so few dies is compatible with Sophytos numismatically proclaimed leadership being of short duration and/or limited scope.